Analysis of Envelope Glycoprotein (E2) of Hepatitis C Virus (HCV) for proposing efficient multi-epitope peptide vaccine based on immuno-informatics approach - Rahman, Adiba (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.